Penerapan Tri Hita Karana untuk Pengembangan Ekowisata Subak Sembung, di Desa Peguyangan, Kecamatan Denpasar Utara - MAHESSA, I PUTU ADITYA; WINDIA, WAYAN; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
The Application of Tri Hita Karana for the Development of Subak Sembung Ecotourism, in Peguyangan Village, North Denpasar District.  Subak is a group of farmer that is originally from Bali. Subak applies Tri Hita Karana teachings to every farming activities in subak's zone. Tri Hita Karana means three reasons of peace living. Tri Hita Karana consists of parahyangan, pawongan and palemahan. Parahyangan is relationship between human and god. Pawongan is relationship between humans. Palemahan is relationship between human and environment. Every single element of Tri Hita Karana is correspond each other. Therefore, by learn about Tri Hita Karana, humans can keep the nature to everlasting and sustainable. Subak Sembung is one of the subak in Bali that applies the teachings of Tri Hita Karana. Besides that, Subak Sembung is already developped into ecotourism since 2014. The implementation of Tri Hita Karana can be guidance for subak to be sustainable and even become the attraction of that subak to become ecotourism destination that often visits by the community that certainly have positive impact to the farmers in Subak Sembung.